Efficacy of Arsenicum Album Phosphorus- Tuberculinum (APT) Protocol in Long-term Prevention of COVID-19 – An Observational Study (Advancements in Homeopathic Research, 2022)
The use of Homoeopathy for preventing epidemic diseases dates back to the time of Hahnemann. Genus epidemicus has generally been considered as the most common and effective method of homoeo prophylaxis of an epidemic disease. But experience shows that it is ineffective to prevent an epidemic disease radically when it is of chronic character in which Hahnemannian antimiasmatic approach has proved to be the most effective as reported in case of prevention of Japanese Encephalitis by using BCT( Belladonna- Calcarea carb Tuberculinum) trio. COVID-19 is now considered as a pandemic of chronic nature. So an antimiasmatic complementary medicinal trio consisting of Arsenic album, Phosphorus and Tuberculinum (APT) has postulated on the basis of symptomatology to prevent COVID- 19 following the same analogy of BCT protocol. These three medicines were administered following APT protocol on one lac eighty-five thousand people from May 2020 to June 2021 and followed the incidence of COVID-19 during this period among these group of people. Observational study reveals that most (about 98-99%) of them have not suffered from COVID-19 even during the second wave. Only a few persons became COVID-19 positive but suffered from mild symptoms. Very few persons having comorbidities were hospitalized, but no death has reported. This shows the potential benefit of APT intervention protocol as homoeoprophylaxis for the present endemo epidemic type of COVID-19, and hence it may be considered as a feasible strategyfor its long-term prevention.
Keywords: Genus epidemicus; Japanese Encephalitis; COVID-19; BCT; APT; Antimiasmatic complementary trio